Sikhism and National Integration - Singh, Pritam (Journal of Dharma, 1983)
Integration of -different strands of social fabric was and still remains a major concern of the Sikh faith. The founder of Sikh faith, Guru Nanak, appears to have arrived at the conclusion quite early in his career that the segregatory instinct had become an in-built part of the Indian ethos and two important factions were contributing substantially towards the perpetuation of that state of affairs. These were : (a) the availability of religious validation to invidious distinctions between man and man, on the basis of birth, and (b) absence of any meaningful dialogue and understanding between different faiths.